Produção e qualidade de melão rendilhado sob diferentes substratos em cultivo protegido - Melo, Danilo Mesquita [UNESP]; Castoldi, Renata [UNESP]; de Oliveira Charlo, Hamilton Cesar; Galatti, Francine de Souza [UNESP]; Braz, Leila Trevisan [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2012)
This paper aimed to evaluate the performance of hybrids of muskmelon on different substrates. Five substrates were evaluated: S(1) = coconut husk fiber, S(2) = sand; S(3) = 1/2 sand and 1/2 crushed of sugarcane, S(4) = 1/2 sand and 1/2 of peanut shell, and S(5) = 1/3 sand, 1/3 of crushed sugarcane and I of peanut shell and four hybrids of muskmelon (Bonus N(o). 2, Louis, Fantasy Jab and 2007 # 16). The plants were cultivated in plastic pots of 13 dm(3), which were filled with these substrates; they were arranged in plants spacing of 1,0 x 0,5 m between plants. The Fertirrigation was done by dripping, using a nutrient solution for the culture. The experimental design was a randomized blocks, in a 5 X 4 factorial design with four replications. The characteristics evaluated were: total production, average transverse and longitudinal diameter of fruit, fruit shape index; mesocarp thickness; average transverse and longitudinal diameter of the locule; index format locule; mass of fresh fruit; soluble solids, pH; titratable acidity; C vitamin; firmness of flesh; tracery of shell; and maturation index. The optimal substrate for muskmelon cultivation is a combination of 50% sand + 50% peanut shell. The hybrid Fantasy performed better compared to other hybrids.

Este trabalho teve por objetivo avaliar o desempenho de híbridos de melão rendilhado em diferentes substratos. Para tanto, foram avaliados cinco substratos: S1 = fibra da casca de coco; S2 = areia; S3 = ½ areia e ½ bagaço de cana-de-açúcar; S4 = ½ areia e ½ casca de amendoim; e S5 = ⅓ areia, ⅓ bagaço de cana-de-açúcar e ⅓ casca de amendoim, e quatro híbridos de melão rendilhado (Bônus n° 2, Louis, Fantasy e Jab 2007#16). As plantas foram conduzidas em vasos plásticos de 13 dm3, os quais foram preenchidos com os referidos substratos, dispondo as plantas em espaçamento de 1,0 X 0,5 m. A fertirrigação foi realizada por gotejamento, utilizando-se a solução nutritiva recomendada para a cultura. O delineamento experimental foi o de blocos casualizados, em esquema fatorial 5 x 4, com quatro repetições. As características avaliadas foram: produção por planta; diâmetro médio transversal e longitudinal do fruto; índice de formato de fruto; espessura do mesocarpo; diâmetro médio transversal e longitudinal do lóculo; índice de formato do lóculo; massa média do fruto; sólidos solúveis; pH; acidez titulável; vitamina C; firmeza do fruto; rendilhamento da casca; e índice de maturação. A melhor opção de substrato, para cultivo de melão rendilhado é a combinação de areia e casca de amendoim em partes iguais, sendo o híbrido Fantasy é o mais recomendado para ser cultivado nestes substratos.
Production and quality of muskmelon plants grown in different substrates at protected cultivation
Keywords: Cucumis melo; Protected cultivation; Peanut shell; Crushed sugarcane; Coconut fiber